Faktor-Faktor yang Mempengaruhi Produk Domestik Bruto (PDB) di Indonesia - Risma, Okta Rabiana; Sari, Yunidar Purnama; Ertika, Yenny; Shifa, Mutiara (Universitas Teuku Umar, 2024)
The purpose of this research is to determine how the influence of money supply, inflation and interest rates on gross domestic product in Indonesia. This research is a quantitative research with multiple linear regression models. The data from 2000 to 2022 with Gross Domestic Product (GDP) as the dependent variable and the Money Supply, Inflation and Interest Rates as independent variables. The results of this research is partially, the money supply and interest rates have a significant effect on gross domestic product, while inflation is not. Then, simultaneously (together), the three variables have a significant effect on Gross Domestic Product (GDP).